PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN REPRESENTASI MATEMATIS SISWA KELAS VII3 SMP NEGERI 3 PEKANBARU - Cesilia, Sindy; Hutapea, Nahor Murani; Anggraini, Rini Dian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to improve the learning process and the student’s mathematical representation skill by applying Problem Based Learning model. The research subject were 39 students of class VII3 SMPN 3 Pekanbaru. This study was conducted in the odd semester of the academic year 2019/2020. This research is Classromm Action Research with two cycles and each of cycle has four stages: planning, implementation, observation, and reflection. Data used in this research are qualitative (Teacher and Student Activity Sheets) and quantitative data (Mathematical Representation Tests). The research instuments consists of learning device (Syllabus, Lesson Plans, and Student Activity Sheets) and instruments for data collecting (Observation Sheet and Mathematical Representation Tests). The data collection technique of this reseacrh are observation by using qualitative analysis and the mathematical representation test was analyzed by using quantitative analysis. Based on analysis of teacher and student activity sheets was obtained that implementation of learning process on cycle II better than cycle I. The result of mathematical representation skill show that score of student’s mathematical representation skill in the first test was 46,39 (low) then it increased to 65,89 (moderate) on cycle I and 78,91 (high) on cycle II. This study concludes that the implementation of Problem Based Learning model improves the learning process and improve the student’s Mathematical Representation Skill at class VII3 SMPN 3 Pekanbaru.Key Words : Problem Based Learning, Mathematical Representation Skill, Learning Process